(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Guava (Psidium guajava L.) is a perishable and climacteric fruit. The peel surface of guava is soft. During transportation, guava surface is rupture lack of proper packaging. Two types of corrugated fibre board (CFB) cartons of 7 and 5 ply and one type of wooden box were designed and fabricated for transportation of guava in Farm Machinery and Postharvest Process Engineering (FMPE) Division, Bangladesh Agricultural Research Institute, Gazipur in 2013. The dimensions of the cartons were 513 x 300 x 240 mm and 400 x 300 x 300 mm. The 7 ply cartons of both the size were found better than those of 5 ply cartons in terms of static load bearing capacity. The carton of 513 x 300 x 240 mm was better than that of second one. The holding capacities of these cartons were about 18-20 kg of guava. The static load bearing capacities of both the cartons of 7 and 5 ply cartons were 90 and 70 kg, respectively. Green matured guava was harvested, sorted and packed in different packages, such as bamboo basket, wooden box, plastic crate, and CFB cartons. They were transported from Sharupkhati of Barisal to Gazipur by a track. Then the guava packages were opened in FMPE Division, BARI, Gazipur and stored at ambient temperature (28.8 ± 2°C) and humidity (87± 2%) for 8 days. The highest shelf-life of guava was found in wooden box without wrapping and the lowest shelf-life was in CFB cartons with polyethylene (0.05 mm) having 2% perforation. Wooden box was found suitable as packaging material for transportation of guava in terms of freshness, shelf-life, and packaging cost. Packaging cost of CFB cartons was higher followed by that of plastic crate, wooden box, and bamboo basket. Packaging costs of plastic crate and wooden box were cheaper than those of CFB cartons and bamboo basket. Plastic crate and wooden box should be used for local market to transport the fruits. CFB carton may be used for export market or supper market. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20437 Bangladesh J. Agril. Res. 39(2): 337-350, June 2014